2016
DOI: 10.5120/cae2016652055
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Effect on Multicrystalline Photovoltaic Module in Western Rajasthan, India

Abstract: General TermsMulticrystalline Photovoltaic Module, Solar Energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…The results of analyses clearly show that dc power obtained at cell temperature 50 o C is far greater than obtained at cell temperature 25 o C. P dc as high as 86.71 KW is obtained at 62 o C cell temperature while P dc obtained at 25 o C cell temperature is insignificant. The result is in accordance to paper [2] where it was concluded that dc output voltage shows negative temperature coefficient for cell temperature greater than 52 o C and not 25 o C. The existing literature and even manufacturers do specify negative temperature coefficient for maximum power output (P max ) with reference to 25 o C cell temperature. The value of temperature coefficient for P max for the module that has been used in the plant is -0.447 %/ o K as shown in table number 2.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The results of analyses clearly show that dc power obtained at cell temperature 50 o C is far greater than obtained at cell temperature 25 o C. P dc as high as 86.71 KW is obtained at 62 o C cell temperature while P dc obtained at 25 o C cell temperature is insignificant. The result is in accordance to paper [2] where it was concluded that dc output voltage shows negative temperature coefficient for cell temperature greater than 52 o C and not 25 o C. The existing literature and even manufacturers do specify negative temperature coefficient for maximum power output (P max ) with reference to 25 o C cell temperature. The value of temperature coefficient for P max for the module that has been used in the plant is -0.447 %/ o K as shown in table number 2.…”
Section: Introductionsupporting
confidence: 73%
“…With reference to cell temperature 25 o C, the short circuit current (I sc ) increases in direct proportion to irradiance while open circuit voltage (V oc ) undergoes modest positive change. At the same time, with increase in cell temperature above 25 o C, V oc decreases substantially while the short circuit current increases only slightly [1].The result is that power output decreases with increase in cell temperature above 25 o C. However in one of the paper entitled "High Temperature Effect on Multicrystalline Photovoltaic Module in Western Rajasthan, India", it has been shown that dc output voltage does not decrease with increase in cell temperature above 25 o C instead stable and high dc output is obtained only when cell temperature is greater than 50 o C [2]. The results of the above paper are further verified by the work done in this paper.…”
Section: Introductionmentioning
confidence: 91%
“…al. showed that Mono-crystalline and Amorphous solar photovoltaic module gives best performance at low humidity and cell temperature around 40 o C for the climatic conditions of Qatar [19]. Garg, JB showed positive effect of ambient and cell temperature on dc voltage up to 38 o C and 50 o C respectively [20]. In another paper [21] Garg, JB showed significant positive effect of cell temperature in 49 o C to 62 o C range and that V dc attains nearly constant and high value only at high cell temperature.…”
Section: Introductionmentioning
confidence: 97%
“…This paper illustrates comprehensive study of real field data to analyse the effect of high cell temperature and POA on the dc voltage of a grid connected multicrystalline module and to estimate temperature coefficient for multicrystalline module in real field conditions which is far different from laboratory conditions. The work done is extension of my previous two papers [4,5]. In previous paper [4] dc voltage was analysed with respect to ambient temperature and GHI (Global Horizontal Irradiance) but results show that V dc has better correlation with cell temperature and POA.…”
mentioning
confidence: 94%
“…The work done is extension of my previous two papers [4,5]. In previous paper [4] dc voltage was analysed with respect to ambient temperature and GHI (Global Horizontal Irradiance) but results show that V dc has better correlation with cell temperature and POA. The results are significant and consistent with the previous results.…”
mentioning
confidence: 94%